Tissue Engineering Auricular Cartilage Using Late Passage Human Auricular Chondrocytes. (April 2018) - Bernstein, Jaime L.; Cohen, Benjamin P.; Lin, Alexandra; Harper, Alice; Bonassar, Lawrence J.; Spector, Jason A.
Abstract : Purpose: The significant shortcomings associated with current autologous reconstructive options for auricular deformities have inspired great interest in a tissue engineering solution. A major obstacle in the engineering of human auricular cartilage is the availability of sufficient autologous human chondrocytes. A clinically obtainable amount of auricular cartilage tissue (ie, 1 g) only yields approximately 10 million cells, where 25 times this amount is needed for the fabrication of a full-scale pediatric ear. It is thought that repeated passaging of chondrocytes leads to dedifferentiation and loss of the chondrogenic potential. However, little to no data exist regarding the ideal number of times that human auricular chondrocytes (HAuCs) can be passaged in a manner that maximizes the cellular expansion while minimizing dedifferentiation. Methods: Human auricular chondrocytes were isolated from discarded otoplasty specimens. The HAuCs were then expanded, and cells from passages 3, 4, and 5 were encapsulated into discs 8 mm in diameter made from type I collagen hydrogels with a cell density of 25 million cells/mL. The constructs were implanted subcutaneously in the dorsa of nude mice and harvested after 1 and 3 months for analysis. Results: Constructs containing passages 3, 4, and 5 chondrocytes all maintained their original cylindrical geometry. After 3 months in vivo, the diameters of the P3, P4, and P5 discs were 69 ± 9%, 67 ± 10%, and 73 ± 15% of their initial diameter, respectively. Regardless of the passage number, all constructs developed a glossy white cartilaginous appearance, similar to native auricular cartilage. Histologic analysis demonstrated development of an organized perichondrium composed of collagen, a rich proteoglycan matrix, cellular lacunae, and a dense elastin fibrin network by Safranin-O and Verhoeff stain. Biochemical analysis confirmed similar amounts of proteoglycan and hydroxyproline content in late passage constructs when compared with native auricular cartilage. Conclusions: These data indicate that late passage HAuCs (up to passage 5) form elastic cartilage that is histologically, biochemically, and biomechanically similar to native human elastic cartilage and have the potential to be used for auricular cartilage engineering. Abstract : Supplemental digital content is available in the text.